Analysis of Force Distribution of Four Rows of Bolts in Aircraft Fitting Joint. (14th July 2021) - Sun, Yifang; Grebenikov, O. G.; Li, Chenghu
Abstract : With the help of 3D modeling software and finite element analysis software, the force distribution of four rows of bolts in the aircraft fitting joint is obtained in this paper. In 3D modeling software, the solid model is segmented according to the area and height of the center of gravity of the cross-section. In finite element analysis software, the beam elements are used to replace the segmented model to obtain the internal force applied at the end of the segmented model and the stress-strain state of each segment is calculated according to the internal force applied at the end of each segment. Finally, the force distribution of the four rows of bolts is obtained according to the average force difference on the center section between the bolt rows. In order to ensure the validity of this step-by-step calculation result, it was compared with the entire calculation result. It can be concluded that the force distribution of the two calculations is consistent. Under the working conditions of the fitting joint (130 MPa), the force distribution coefficients of the four rows of bolts are 0.182, 0.215, 0.197, and 0.12. Therefore, it is feasible to use the step-by-step method to calculate the force distribution of the four rows of bolts in the fitting joint. Compared with the entire calculation, the step-by-step calculation has the advantages of less calculation amount and faster calculation speed.